Quantifying 6D tumor motion and calculating PTV margins during liver stereotactic radiotherapy with fiducial tracking - Sun, Xingru; Dai, Zhitao; Xu, Meiling; Guo, Xueling; Su, Huanfan; Li, Yang (Frontiers in Oncology, 2022)
Objective Our study aimed to estimating intra-fraction 6D tumor motion with rotational correction and the related correlations between motions of different dimension, as well as to quantify adequate anisotropic clinical target volume (CTV)-to-planning target volume (PTV) margins during stereotactic liver radiotherapy based on fiducial tracking. Methods A cohort of 12 patients who were implanted with 3 or 4 golden markers were included in this study, and 495 orthogonal kilovoltage (KV) pairs of image acquired during the first fraction were used to extract the spacial position of each gold marker.Translational and rotational motions of tumor were calculated based on the marker coordinates by using an iterative closest point (ICP) algorithm. Moreover, the Pearson product-moment correlation coefficients (r) were applied to quantify the correlations between motions with different degree of freedom (DoF).The population mean displacement (MP ), systematic error (Σ) amd random error (σ) were obtained to calculate the intrafractional PTV margins based on Published recipes. Results The mean translational variability of tumors were 0.56, 1.24 and 3.38 mm in the left-right (X), anterior-posterior (Y),and superior-inferior (Z) directions, respectively. The average rotational angles θX, θY and θZ around the three coordinate axes were 0.88, 1.24 and 1.12◦, respectively. |r| > 0.4) were obtainted between Y -Z, Y -θZ, Z-θZ and θX-θY . The PTV margins calculated based on 13 published recipes in X, Y and Z directions were 1.08, 2.26 and 5.42 mm , and the 95% confidence interval of them were (0.88,1.28), (1.99,2.53) and (4.78,6.05), respectively. Conclusions The maximum translational motion was in SI direction, and the largest correlation coefficient of Y -Z was obtained. We recommend margins of 2, 3 and 7 mm in left-right, anterior- posterior, and superior-inferior directions, respectively.